Bipolaris omanensis, a novel saprobic species of Bipolaris from Oman based on morphology and sequence data - Al Dughaishi, Sumaiya; Maharachchikumbura, Sajeewa S. N.; Al-Sadi, Abdullah M. (Phytotaxa, 2018)
Bipolaris species are responsible for important cereal diseases, worldwide and are often isolated as endophytes as well as saprobes. We are investigating the fungi in Oman. In this paper, we report a novel taxon of Bipolaris, collected from the leaves of Hibiscus rosa-sinensis, during the survey. The taxon is shown to be novel based on morphological and sequence data and introduced here as Bipolaris omanensis sp. nov. Bipolaris omanensis forms a sister clade to B. cookei based on the combined sequence analysis of internal transcribed spacers (ITS) and partial glyceraldehyde-3-phosphate dehydrogenase (GAPD) region, being distinct from the latter species in having shorter conidiophores, narrower conidia and having a higher number of septa.